Physicochemical and protein characterization of lima bean (Phaseolus lunatus L) seed - Estiasih, T. (2024)
Lima bean (Phaseolus lunatus L) is native to Latin America and has spread out worldwide, thus having a high level of diversity. The lima bean seed from a specific region might have different characteristics from others. This study was aimed to characterize the physicochemical and protein of the dry seed of lima bean from Indonesia based on its solubility, electrophoretic pattern, and amino acid profile. The result showed that carbohydrate (68.89±1.55%) was the major component, with starch (41.96±1.10%) as the predominant. The amylopectin was higher than amylose. Dietary fibre (27.87±0.37%) was significant and dominated by insoluble one (25.47±0.32%). The fat content (1.15±0.04%) was low and ash (3.67±0.47%) comprised of magnesium, phosphorus, potassium, calcium, and iron with the content of 184, 75, 38, 11, and 10 mg/100 g, respectively. Total phenolic compounds of this seed were 1.29±0.02 mg/g, phytic acid 11.57±0.03 mg/g, saponins 16.84±0.42 mg/g, and trypsin inhibitors 36.07±0.11 TIU/g. HCN was found significantly at 30.99±0.29 ppm. Oligosaccharides were 5.93±0.29% that comprised of raffinose 1.22±0.08% and stachyose 4.61±0.21%. Protein content was moderate (15.93±0.55%) that comprised of albumin 18.47±0.62%, globulin 56.20±2.00%, prolamin 3.14±0.20%, and glutelin 22.69±1.60%. The molecular weight of this protein was 10-141 kDa with 12 polypeptides. Globulin had 12 polypeptides of 10 to 124 kDa. Albumin had 18 to 116 kDa molecular weights, while glutelin had six polypeptides of 13 to 109 kDa. Prolamin did not have visible polypeptides. Lysine, leucine, valine, and phenylalanine were the primary essential amino acids with high lysine but low methionine and cysteine. In conclusion, lima bean seed is a source of carbohydrates and minerals, with a moderate protein content dominated by the globulin. The polypeptide profile of lima bean seed is varied depending on the protein fractions. The occurrence of antinutrition might hinder its utilization as a protein source. HCN as a toxicant should be removed to obtain a safe seed for consumption.